FORMULASI SEDIAAN NUTRASETIKAL POWDER DRINK KULIT BAWANG MERAH BREBES (Allium cepa L. var. aggregatum) - Febriani, Alik Kandhita; Balfas, Rifqi Ferry; Purwanti, Yunika; Maesarah, Ifani (Parapemikir : Jurnal Ilmiah Farmasi, 2024)
Indonesia, known for its rich biodiversity, boasts many medicinal plants with significant development potential. One such plant is shallots (Allium cepa L.), a valuable vegetable commodity that plays an important role in society due to its economic and nutritional value. Shallots are rich in various secondary metabolites, including flavonoids, tannins, saponins, essential oils, kaempferol, flavonglycosides, phloroglucin, dihydroaliin, cycloaliin, metiallin, quercetin, and polyphenols, with sulfur also present in the tubers. This research aims to formulate shallot skin into a nutraceutical powder drink. Using experimental laboratory methods, we formulated the shallot skin powder drink and conducted physical tests on the preparation. The results indicated that while the formulations met the criteria for ash content, pH, dissolution time, flow time, and compressibility, not all formulas satisfied the requirements. Specifically, the shallot skin powder drink did not meet the standards for water content and angle of repose.